Implementation of the K-Nearest Neighbor (KNN) Algorithm in Making a Web-Based Article Topic System - Ramadhani, Fanny (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2022)
This study aims to apply the K-Nearest Neighbor algorithm in making an article topic determination system. The K-Nearest Neighbor algorithm is one of the oldest and most popular NN-based methods for categorizing text. In determining class label predictions on test data it is determined by the value of k which represents the number of nearest neighbors. Of the k closest neighbors selected, voting is carried out by selecting the class with the most number as the predicted class label on the test data. Classification is considered the best method in processing when the training data is closest to the object. The way the KNN works requires determining the input in the form of training data, test data and k values.